Eksplorasi Sejarah dan Arsitektur Candi Kembar Batu: Kajian Arkeologi dan Nilai Budaya - Angelica, Rytu Aureli; Fahreza, M. Rifki; Fikri, M. Azizul; Prayuda, Farhan David; Syamsiah, Syamsiah (Lembaga Pendidikan dan Penelitian Manggala Institute, 2024)
The Candi Kembar Batu, located in Muaro Jambi, is an ancient temple complex that represents the cultural and historical legacy of the ancient Jambi Kingdom. This article explores the history, architecture, and archaeological significance of the site, as well as its cultural values. The research method used includes a historical approach, analysis of archaeological data, and evaluation of the site’s architecture. Findings indicate that Candi Kembar Batu reflects a blend of Hindu-Buddhist influences and local Jambi traditions. The temple's unique design and its surroundings provide valuable insights into the religious, social, and cultural life of ancient communities in the region. The study also highlights the temple's potential role in the broader context of Southeast Asian religious architecture.